A união vai fazer a força: caminhos possíveis para o fortalecimento da Educação Permanente em uma Unidade Básica de Manaus - Nascimento, Annelise Rodrigues do (Brasil, 2023)
This action research emerges from the encounters and affective connections experienced by us as students and participants of the PET-Health program, in the vibrant daily life of a Basic Health Unit located in the outskirts of the city of Manaus. The main objective is to report the experience of conversation circles held with the workers of the Vila da Prata Basic Health Unit, from the perspective of Health Communication. In this way, the text goes beyond words and echoes the shared experiences, the constructed dialogues, the inhabited territory, and the attentive gazes cast upon the intricate work processes that unfold in the constant frenzy of everyday life. In this journey, we share the thoughts of Deleuze and Guattari, using Cartography as a possible methodological path. Throughout the discussion, we emphasize the integration between education, service, and community, engaging with the contents of the workshops and interviews conducted. Finally, we understand the importance of expanding the discussion on Permanent Education in Health, exploring new perspectives and horizons.